Endogenous metabolite, kynurenic acid, attenuates nonalcoholic fatty liver disease via AMPK/autophagy‐ and AMPK/ORP150‐mediated signaling. Issue 7 (7th December 2020) - Pyun, Do Hyeon; Kim, Tae Jin; Kim, Myeong Jun; Hong, Soon Auck; Abd El‐Aty, A. M.; Jeong, Ji Hoon; Jung, Tae Woo
Abstract: Endoplasmic reticulum (ER) stress plays a causative role in the development of nonalcoholic fatty liver disease (NAFLD). Kynurenic acid (KA) is a tryptophan metabolite that has been shown to exert anti‐inflammatory effects in macrophages and endothelial cells. However, the role of KA in ER stress‐associated development of NAFLD has not been fully explored. In the current study, we observed decreased KA levels in the serum of obese subjects. Treated hepatocytes with KA attenuated palmitate‐induced lipid accumulation and downregulated lipogenesis‐associated genes as well as ER stress markers in a dose‐dependent manner. Furthermore, KA augmented AMP‐activated protein kinase (AMPK) phosphorylation, oxygen‐regulated protein 150 (ORP150) expression, and autophagy markers. The small interfering RNA‐mediated suppression of AMPK and ORP150, or 3‐methyladenine also abrogated the effects of KA on ER stress and lipid accumulation in hepatocytes. In accordance with in vitro observations, KA administration to mice fed a high‐fat diet ameliorated hepatic lipid accumulation and decreased the expression of lipogenic genes as well as ER stress. Moreover, KA treatment increased hepatic AMPK phosphorylation, ORP150 expression, and autophagy related markers in mouse livers. Knockdown of AMPK using in vivo transfection mitigated the effects of KA on hepatic steatosis and ER stress as well as autophagy and ORP150 expression. These results suggest that KA ameliorates hepatic steatosis via the AMPK/autophagy‐ and AMPK/ORP150‐mediated suppression of ER stress. In sum, KA might be used as a promising therapeutic agent for treatment of NAFLD. Abstract : (1) Kynurenic acid (KA) attenuates lipid accumulation and expression of lipogenic genes in hepatocytes (2) KA ameliorates ER stress in hepatocytes (3) AMPK/autophagy and AMPK/ORP150 pathways contribute to the effects of KA on NAFLD.